2016
DOI: 10.1007/s11064-016-2022-x
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Hyperbaric Oxygen on Cognitive Impairment Induced by d-Galactose in Mice

Abstract: Memory decline is characteristic of aging and age-related neurodegenerative disorders. This study was designed to investigate the protective effect of hyperbaric oxygen (HBO) against cognitive impairment induced by D-galactose (D-gal) in mice. D-gal was intraperitoneally injected into mice daily for 8 weeks to establish the aging model. HBO was simultaneously administered once daily. The results indicate that HBO significantly reversed D-gal-induced learning and memory impairments. Studies on the potential mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 46 publications
2
36
0
Order By: Relevance
“…The rate of binucleated hepatocytes increased with ageing [31]. D-Gal apparently increased the binuclear rate of the liver [32] but decreased the white-pulp proportion of spleen [33] and the surviving neurons of the hippocampus [34] in the previous studies. D-Gal-induced mimetic ageing is associated with an increase in oxidative stress [27,28].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The rate of binucleated hepatocytes increased with ageing [31]. D-Gal apparently increased the binuclear rate of the liver [32] but decreased the white-pulp proportion of spleen [33] and the surviving neurons of the hippocampus [34] in the previous studies. D-Gal-induced mimetic ageing is associated with an increase in oxidative stress [27,28].…”
Section: Discussionmentioning
confidence: 64%
“…Oxidative stress promoted cellular senescence [35]. A large number of studies have used the D-gal-induced ageing model for screening of anti-ageing compounds [26][27][28][29][32][33][34]. In our study, the D-gal-induced ageing model was well-established…”
Section: Discussionmentioning
confidence: 92%
“…For histomorphological examinations, all samples were xed in 4% formaldehyde buffer followed by embedding in paraffin and slicing longitudinally, with 5 mm-thick sections obtained for hematoxylin-eosin staining for histomorphological analysis. 4,5 Furthermore, liver and kidney histopathological score was performed. Briey, the degree of necrosis in liver was expressed as the mean of twelve different elds within each classied on a scale of 0-3 (normal-0, mid-1, moderate-2, severe-3).…”
Section: Hematoxylin and Eosin (He) Stainingmentioning
confidence: 99%
“…The free radical theory of aging posits that oxidative stress and reactive oxygen species (ROS) accumulation-induced cell and tissue damage play a critical role in the pathological process of aging. 4 Plenty of evidence has demonstrated that oxygen free radicals, which are generated during metabolism and energy production in the body, are closely related to the regulation of signal transduction and gene expression as well as redox homeostasis. 5 However, high levels of ROS can cause the peroxidation of membrane lipids, and damage to DNA, proteins and phospholipids, eventually resulting in cellular injury, apoptosis and inammation.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperbaric oxygen (HBO) therapy, treatment providing 100% oxygen at a pressure greater than that at sea level, can be considered as one of these methods. In this regard, studies documented that HBO have neuroprotective effects against traumatic brain and spinal cord injury [ 11 , 12 ], ischemic brain and spinal cord injury [ 13 , 14 ], neurodegenerative disorders [ 15 , 16 ], oxidative damage in neuronal culture [ 17 ], and neuropathic pain [ 18 ]. Recently, HBO has been demonstrated to improve nerve regeneration [ 19 , 20 ] following peripheral nerve injury.…”
Section: Introductionmentioning
confidence: 99%